The impact of governmental COVID‐19 measures on manufacturers' stock market valuations: The role of labor intensity and operational slack - Chen, Lujie; Li, Taiyu; Jia, Fu; Schoenherr, Tobias (Journal of Operations Management, 2023)
AbstractThis study investigates the impact of the Chinese government's Level I emergency response policy on manufacturers' stock market values. We empirically examine the roles of human resource dependence (labor intensity) and operational slack within the context of supply chain resilience. Through an event study of 1357 Chinese manufacturing companies, we find that the government's emergency response policy triggered statistically significant positive abnormal returns for manufacturers. However, we also find that there exists a negative impact on abnormal returns for manufacturers that are labor‐intensive, giving rise to arguments based in resource dependence theory. In addition, the results indicate the positive role played by operational slack (e.g., financial and inventory slack) in helping manufacturers maintain operations and business continuity, effectively mitigating risks and adding to the manufacturers' resilience. With these findings, we contribute to operations and supply chain management by calling attention to the importance of human resource redundancy while at the same time identifying financial slack and inventory as supply chain resilience strategies that were able to mitigate pandemic‐related risks.